English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2x^2 + x - 1 = 0
ax^2 + bx + c = 0
a=2, b=1, c=-1

x = -b +- square root(b^2 - 4ac)/2a
= -1 +- square root(1^2 - 4(2)(-1)
= -1 +- square root(9)/2*2
= -1 +- square root(9)/4

I am pretty sure I did this correct; however, since the square root of 9 is 3 would the answer be
= -1 +- 3/4
or would it be =-1 +- square root(3)/4

2007-03-04 04:00:52 · 2 answers · asked by Anonymous in Science & Mathematics Mathematics

2 answers

2x² + x - 1

Let

a = 2

b = 1

c = - 1

- - - - - -

Quadratic formula

x = - b ± √b² - 4ac / 2a

x = - 1 ± √(1)² - 4(2)( - 1) / 2(2)

x = - 1 ± √1 - ( - 8) / 4

x = - 1 ± √1 + 8 / 4

x = - 1 ± √9 / 4

x = - 1 ± 3 / 4

- - - - - - - -

Solving for +

x = - 1 + 3 / 4

x = 2 / 4

x = 1/2

x = 0.5

- - - - - - - -

Solving for -

x = - 1 - 3 / 4

x = - 4/4

x = - 1

- - - - - - -s-

2007-03-04 04:47:22 · answer #1 · answered by SAMUEL D 7 · 0 0

2x^2 + x - 1 = 0
ax^2 + bx + c = 0
a=2, b=1, c=-1

x = (-b +- square root(b^2 - 4ac))/2a
x= (-1 +- square root(1^2 - 4(2)(-1)))/2*2
x= (-1 +- square root(9))/2*2
x= (-1 +- square root(9))/4
x= (-1 +- 3)/4
x= (-4/4) or (2/4)
x= -1 or 1/2

2007-03-04 12:14:55 · answer #2 · answered by paul_gchs 4 · 0 0

fedest.com, questions and answers